Depression and Associated Suicidal Behaviour in Children and Adolescents: Current Views and the Problem State Part 1 - L.V. Pypa; S.V. Rymsha; R.V. Svistilnik; Yu.N. Lisitsa (Zaslavsky O.Yu., 2014)
There has been performed the analytical analysis of the world literature dedicated to the epidemiology, etiology, current approaches to the pathogenesis, clinical picture and diagnosis criteria for the depressive disorders in children and adolescents as well as the associated suicidal behavior and the social significance of this disease with its consequences. Key recommendations on the treatment and prophylaxis of depression in children and adolescents according to the last evidence-base European and American guidelines are considered.